(untitled) (Bangladesh Medical Journal, 2016)
A bicuspid aortic valve (BAV) can be a serious disorder of heart valve in which the valve only has two leaflets or flaps that control blood flow through the heart. Between one and two percent of all people have this defect and it affects more men than women. This report presents a case of severe aortic stenosis with mild to moderate aortic regurgitation due to bicuspid aortic valve with hypertension. A 37 years old male presented with high record of blood pressure and occasional shortness of breath on exertion. Echocardiography (Color Doppler) revealed severe aortic stenosis with mild to moderate aortic regurgitation due to bicuspid aortic valve with moderately severe concentric LV wall hypertrophy. Surgical treatment (aortic valve replacement) was scheduled based on echocardiography findings. On surgical resection a well defined bicuspid aortic valve was found with calcification and friable valve leaflet. Histopathology of valve tissue shows large areas of calcification. Patient was discharged from hospital on 7th POD with an advice to attend cardiac surgery OPD after 1 month. Aortic valve replacement must be considered in this type of lesion. Bangladesh Med J. 2015 May; 44 (2): 105-108